Identification of Ectoparasites Cause Lesions in Parents Goldfish (Carassius auratus) - Agung S Abadi; Intanurfemi B Hismayasari; Waliyatun Waliyatun (Jurusan Perikanan dan Kelautan, 2021)
The purpose of this study was to determine the cause of bruises on the body of the mother goldfish (Carassius auratus). Fish were obtained from the Research Installation of Freshwater Aquaculture, Marine and Fisheries Polytechnic Sorong. The initial diagnosis of fish is weak, decreased appetite, and has bruises in almost all parts of the body. Fish were isolated and identified at the Sorong Fish Quarantine and Quality Control Station. Examination starts from the head, gills, body and tail. The results of identification using a microscope obtained the types of ectoparasites in the form of, Dactylogyrussp, Ergasilus sp. Gyrodactylus sp. Lernea cyprinacea, Lernea sp and Trichodina sp.